Designing Comprehensive Independent Learning Interactive Multimedia and its Resources Demands - Enjang Akhmad Juanda; Ali Ibnun Nurhadi (Universitas Ahmad Dahlan, 2014)
Generally, multimedia project refers to a combination of two or three types of media, such as texts, images, animations, applications, and videos, and is easily decompiled. This research produces interactive multimedia with five types of media using ActionScript. Using an external XML file as the connector between interface and contents, this interactive multimedia becomes reusable and developable. This multimedia project is flash based with the extensions *.swf and *.exe. To protect from decompiling, the project uses layered encryption combined with As3Crypto encryption. Based on test results, Sothink SWF Decompiler software cannot decompile and display all the properties of the project. In this research ,the analysis highlights multiplatform, standalone, media types, content types, exercises system, responsive, reusability, developability, energy efficiency, layered encryption and independent learning. Based on test results, the project has been tested and participants declared that they can use all contents and navigations easily and it ran normally on the devices used.